On Some Issues of Post-War World Order (speech at the annual meeting of the russian historical society on september 9, 2015) - A. V. Torkunov (MGIMO University Press, 2015)
Abstract: 70th anniversary of our victory in the Great Patriotic War and large-scale national and international events marking the end of the Second World War caused an unprecedented wave of interest in the history of the war and the problems of post-war world order. There are new estimates of the war differing from previous interpretations of events, many of which, apparently, are connected with the political situation. In this regard, I would like to focus on two important issues that seem to me to be underestimated nowadays - institutional component of the postwar world, and the specifics of the Asia-Pacific order at the end of the war.